2021
DOI: 10.1155/2021/6642246
|View full text |Cite
|
Sign up to set email alerts
|

Association between Monocyte to High-Density Lipoprotein Cholesterol Ratio and Nonalcoholic Fatty Liver Disease: A Cross-Sectional Study

Abstract: Background. The aim of the present study was to investigate the association between monocyte to high-density lipoprotein cholesterol ratio (MHR) and nonalcoholic fatty liver disease (NAFLD) in Chinese population. Methods. We enrolled 14189 individuals who attended their annual health examinations in the study. We performed the anthropometric and laboratory measurements and diagnosed NAFLD by hepatic ultrasonography without evidence of other etiologies of chronic liver disease. Student’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
3
14
1
Order By: Relevance
“…In our research, the NAFLD group had a median age of 45 years, with 72.5% of males and 27.5% of females, which was consistent with that reported by Huang et al ( 24 ). The study showed that the BMI of the NAFLD group was significantly higher than that of the healthy control group, consistent with Jia’s study ( 21 ), which suggested that overweight or obesity is a risk factor for NAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…In our research, the NAFLD group had a median age of 45 years, with 72.5% of males and 27.5% of females, which was consistent with that reported by Huang et al ( 24 ). The study showed that the BMI of the NAFLD group was significantly higher than that of the healthy control group, consistent with Jia’s study ( 21 ), which suggested that overweight or obesity is a risk factor for NAFLD.…”
Section: Discussionsupporting
confidence: 92%
“…A recently reported retrospective study involving 409 patients showed that there was a significant positive association between MHR and age, ALT and HOMA-IR values, and the risk of non-alcoholic hepatic steatosis ( 29 ). Huang et al investigated the association between MHR and NAFLD in a Chinese population of 14,189 participants and revealed that MHR was positively associated with the risk of NAFLD diagnosed by hepatic ultrasonography after multivariate logistic regression analysis ( 30 ). Our study draws a similar conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…MHR was also considered as indicators of oxidative stress and systemic inflammatory disease. Several studies reported that MHR showed a powerful predictive value for chronic inflammatory disease like PCOS (10), peripheral artery disease (25), central retinal artery occlusion (26), Parkinson's Disease (11), nonalcoholic fatty liver disease (27), and STelevation myocardial infarction (28). Furthermore, Jiang et al found that MHR was significantly related to all-cause and cardiovascular mortality in the general population independent of established risk factors (9).…”
Section: Discussionmentioning
confidence: 99%